Dose perturbation caused by metallic port in breast tissue expander in proton beam therapy. (18th November 2020) - Zhao, Li; Moskvin, Vadim P; Cheng, Chee-Wai; Das, Indra J
Abstract: Proton beam treatment is being looked favourably now in breast treatment. Tissue expanders are often placed after mastectomy that contains metallic port for saline injection which produces dose perturbations in proton beam therapy with uncertain dosimetry. Dose perturbation for a stainless-steel injection port from a breast implant is investigated in this study. Measurements, Monte-Carlo simulation, and calculated dose distribution of plans based on kVCT and MVCT images are compared. Treatment plans are performed on kVCT and MVCT images to observe the effect of metal artifact from the breast implant. The kVCT based plan underestimates the beam range due to the overestimated water equivalent thickness of the metal ports as a result of image degradation. Compared to the measurement with metal port in the proton beam, the MVCT-based treatment planning provides more accurate dose calculation than the kVCT-based results. The dose perturbation factor calculated from MVCT planning is within 10% of the measurement results while HU corrected kVCT plan still shows dose difference as large as 100% due to the incorrect range pull back calculation caused by the misrepresentation of the volume between the plastic cap and the stainless-steel base. The dose enhancement observed at the metal and solid water interface is as large as 15%, which needs to be accounted for in the planning process if there is a clinical concern. Dose reduction as large as 16% is observed with depth from 1 cm to 4 cm underneath the thickest part of the metallic port whereas lateral dose perturbation is also seen up to 7 mm. The measurement data are supported by the Monte-Carlo simulated results with a maximum dose difference of 6%. It is concluded that if proton beam is used with metallic port, MVCT imaging data is recommended. In lieu of MVCT, DECT, CT scanner with metal artifact reduction software or in the very least, extended HU range should be used to reduce the streaking artifact as well as to produce a more accurate image of the metallic port.